Arthrocladiella mougeotii causing powdery mildew on goji berry plants ( Lycium barbarum and L. chinense ) and mixed infections with Phyllactinia chubutiana in California - Elfar, Karina; Bustamante, Marcelo I; Rooney-Latham, Suzanne; Eskalen, Akif; Miller, Tom (Plant disease, 2024)
Goji berries ( and ) have a rich historical significance in traditional Chinese medicine and have gained popularity as a superfood in Western cultures. From 2021 to 2023, powdery mildew was observed on goji plants of both species in community and residential gardens in Yolo County, California (USA). Disease severity varied from 20 to 100% of infected leaves per plant. Powdery mildew was characterized by the presence of white fungal colonies on both sides of leaves and fruit sepals. Additionally, a brownish discoloration was observed in infected mature leaves, resulting in further defoliation. Morphologically, the fungus matched the description of . The pathogen identity was confirmed by phylogenetic analyses of the rDNA internal transcribed spacer and the 28S rDNA gene sequences. Pathogenicity was confirmed by inoculating healthy plants using infected leaves and successfully reproducing powdery mildew symptoms after 28 days (22°C, 60% RH), with colonies confirmed by morphology. Control leaves remained symptomless. Co-infection with was detected on plants from two separate gardens, with observed first in late spring (May to June) and later in the summer (July to August). These results revealed that both and constitute causal agents of powdery mildew on goji berry plants, often infecting the same plant tissues simultaneously. To our knowledge, this is the first report of causing powdery mildew on and in California, which provides a better understanding of the etiology of powdery mildew of goji plants in California.